2020
DOI: 10.18433/jpps31501
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Elevation of Cardiac Biomarkers and the Severity of COVID-19 Infection: A Meta-analysis

Abstract: - Purpose: Since December 2019, coronavirus disease 2019 infection has become a global pandemic. The cases of Coronavirus Disease 2019 (COVID-19)-related acute cardiac injury with unknown pathophysiologic mechanism has become increasingly prevalent. However, it is not yet understood how the extent of cardiac injury differs with the intensity of viral infection.  In the current study, we aimed to assess the association between elevated cardiac biomarkers and the severity of COVID-19 infection. Methods: A system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Previous systematic reviews and meta-analyses have reported associations between serum CK-MB concentrations and COVID-19 severity and mortality [ [19] , [20] , [21] , [22] ]. Our meta-analysis has captured more than double the number of studies, 55 vs. 25, and participants, 11,791 vs. 5,626, than the largest previously published meta-analysis [ 21 ]. Furthermore, we investigated possible associations between the observed SMD and a number of biologically and clinically plausible factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous systematic reviews and meta-analyses have reported associations between serum CK-MB concentrations and COVID-19 severity and mortality [ [19] , [20] , [21] , [22] ]. Our meta-analysis has captured more than double the number of studies, 55 vs. 25, and participants, 11,791 vs. 5,626, than the largest previously published meta-analysis [ 21 ]. Furthermore, we investigated possible associations between the observed SMD and a number of biologically and clinically plausible factors.…”
Section: Discussionmentioning
confidence: 99%
“…A number of systematic reviews and meta-analyses on troponin and COVID-19 have been published [ [15] , [16] , [17] , [18] ]. Similarly, meta-analyses have sought to critically appraise the available evidence regarding the clinical role of CK-MB [ [19] , [20] , [21] , [22] ], with the largest meta-analysis identifying a total of 25 studies in 5,626 COVID-19 patients [ 21 ]. While CK-MB is less used in the diagnosis and the monitoring of myocardial necrosis in contemporary clinical practice since the advent of high-sensitivity troponin, additional retrospective and prospective studies have since been published on the associations between serum CK-MB concentrations, COVID-19 severity, and adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory response to COVID-19 leads to increased systemic inflammatory markers and potential abnormal function of vital organ systems, including pulmonary and cardiovascular. We have previously shown that there is significant association between elevated cardiac and inflammatory biomarkers and the severity of COVID-19 ( 22 ). To our knowledge, no meta-analysis has addressed the association between vitamin D levels with cardiac and inflammatory biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Another study has shown prognostic utility of proBNP in a small cohort (102 patients) of severe COVID-19 patients ( 11 ). A meta-analysis on cardiac biomarkers also demonstrated that NT-proBNP was significantly higher in severely ill COVID-19 patients compared with nonsevere cases ( 8 ). Only a few observational studies have not shown B-type natriuretic peptide (BNP) as a marker of clinical significance; although, comparatively, these studies were smaller, relatively racially homogenous, had limited follow-up time, and had significantly fewer days of mechanical ventilation ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 98%